Contributions to Astragalus sect. Dissitiflori in the light of morphological and molecular evidence: a new species and a new resurrect - Pourebrahim, Shima; Kazempour-Osaloo, Shahrokh; Maassoumi, Ali Asghar (Phytotaxa, 2024)
Astragalus sublunatus is described as a new species from semi desert area of Semnan and Tehran provinces. The diagnostic characters and relevant description of the new species are given. It is distinguished from its closely related species, A. sitiens and A. ahangarensis, in having plicate inward leaflets, long and linear-lanceolate terminal leaflet and white petals in living time. It is also distinct from these species by molecular data, and along with them as well as A. bifoliolatus and A. moussavii formed a well-supported lineage. The distribution map and an illustration of the new species are also provided. Meanwhile, three accessions of A. sitiens were phylogenetically distinct from the rest of its conspecific members. They are morphologically well fitted with the characteristics of A. angustatus and thus, it was resurrected as a distinct species.